2019
DOI: 10.1038/s41467-019-13197-z
|View full text |Cite
|
Sign up to set email alerts
|

Band splitting with vanishing spin polarizations in noncentrosymmetric crystals

Abstract: The Dresselhaus and Rashba effects are well-known phenomena in solid-state physics, in which spin–orbit coupling splits spin-up and spin-down energy bands of nonmagnetic non-centrosymmetric crystals. Here, we discuss a phenomenon we dub band splitting with vanishing spin polarizations (BSVSP), in which, as usual, spin-orbit coupling splits the energy bands in nonmagnetic non-centrosymmetric systems. Surprisingly, however, both split bands show no net spin polarization along certain high-symmetry lines in the B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Interestingly, these bands are partially spinpolarized: it can be observed that the top valence bands are only spin-polarized in the vicinity of the K-point even though spin splitting occurs along the whole bandstructure path. This scenario was recently discussed by Liu and coworkers 35 who demonstrated that spin-orbit coupling can lead to spin splittings without spin polarization in non-magnetic materials without inversion symmetry.…”
Section: Heterobilayersmentioning
confidence: 84%
“…Interestingly, these bands are partially spinpolarized: it can be observed that the top valence bands are only spin-polarized in the vicinity of the K-point even though spin splitting occurs along the whole bandstructure path. This scenario was recently discussed by Liu and coworkers 35 who demonstrated that spin-orbit coupling can lead to spin splittings without spin polarization in non-magnetic materials without inversion symmetry.…”
Section: Heterobilayersmentioning
confidence: 84%
“…This contradiction implies that the pseudo--vector 𝑆 !" must vanish (even in spin split bands), as in two--dimensional SnTe thin film [45].…”
mentioning
confidence: 99%
“…Such quasipersistent spin textures [61] (promising for nondephasing spin transport [61,62]), together with large spin splitting, form another prospective aspect. Third, the discovery of different types of spin textures may promote exotic device applications as evidenced by, e.g., linear magnetoelectric effect driven by the "band splitting with vanishing spin polarizations" phenomenon [63]. We are also aware of interesting spin textures and mechanisms for Rashba spin splittings in multiferroic BiCoO 3 with canted spins [64].…”
Section: (B) (Ie With Soc) Using the Simple Expressionmentioning
confidence: 99%